Evaluation of water quality, hydrochemical processes, and health risks associated with spring water in Thulamela Municipality, Limpopo Province, South Africa - Madilonga, Rofhiwa Teresa (My University, 2022)
Groundwater is regarded as one of the most crucial natural resources, globally. In Africa, people have been focusing, extensively, on groundwater, for water supply to meet their daily water needs, especially, in rural areas. This is because the geographic locations of most rural communities are hard to reach, due to them being dispersed and the bad terrain. In South Africa, these conditions have made it difficult and expensive for provision of water services to rural communities. Springs have been widely used for a variety of human needs including recreation, drinking water, domestic water supply and irrigation. In Thulamela Municipality, there are springs located within the Vhembe District in the Limpopo Province, South Africa. This study aimed to evaluate the water quality, potential uses, and health risks associated with spring water in Thulamela Municipality. One hundred and sixty-four water samples were collected from 41 springs between August-September 2020 (dry season) and December-January (wet season) 2020/2021 and analyzed for their physicochemical and microbial characteristics. The analytical data of some physicochemical parameters (pH, Total Dissolved Solids (TDS), Electrical Conductivity, Salinity, Turbidity and Temperature) was determined onsite using Extech multimeter and turbidimeter. All the physiochemical parameters measured complied with the World Health Organisation (WHO) and South African National Standards (SANS) in both seasons, except for turbidity. The concentration of trace elements (Al, V, Mn, Fe, Co, Ni, Cu, Zn, Cr, As, Se, Sr, Mo, Cd, Sn, Sb, Ba, Hg, Pb and Si) were analysed by inductively coupled plasma mass spectrometry (ICP-MS) and major cations (Na, Mg, P, K and Ca) were analysed using inductively coupled plasma-optical emission spectroscopy (ICP-OES). The major and trace metals analysed were recorded in levels below the regulatory limits of WHO and SANS except for Sb in the wet season. Major anions (𝐹−, 𝐶𝑙−, 𝑁𝑂3−, 𝑁𝑂2−, Br, 𝑃𝑂43− and 𝑆𝑂42−) in the spring samples were analysed using Ion Chromatography (IC). The concentrations of 𝐹−,C𝑙−, 𝑁𝑂3−,and 𝑆𝑂42− complied with the regulatory limit while 𝑁𝑂2−, Br, 𝑃𝑂43− exceeded the limits in both seasons. Microbiological parameters (Total Coliform, faecal coliform and E. coli) were tested using Membrane Filtration (MF) method. None of the spring water samples complied with the regulatory guidelines of 0 cfu/100ml set by WHO and SANS, for human consumption. Total coliform were recorded in all of the samples, in both seasons. Faecal coliform showed 85.4% and 95.13% presence in the dry and wet seasons whereas E. coli detected 34.15% in dry season and 58.53% in the wet season. The Water Quality Index (WQI) was also computed based on parameters: Mn, Fe, Ni, Cu, Cr, Cd, Ba, Pb, Mo and Zn. The WQI in Thulamela Municipality showed 100% and 80.04% for dry and wet seasons, respectively of sampled spring water can be regarded as excellent water quality, whereas and 19.51% for dry and wet seasons, respectively are considered as good water quality. The Piper diagram was v determined by three hydrochemical types, namely, Ca-HCO3, mixed Ca-Mg-Cl, and Ca-Cl2 water types in wet and dry seasons. The dominant water type in dry season and wet seasons were Ca-Mg-Cl and Ca-HCO3, respectively. The principal hydrochemical processes shaping the groundwater chemistry are either dilution or mixing. Gibbs plots in all the studied seasons suggested that spring weathering material was the prevailing system controlling the science of the springs at the study area followed by evaporation. Health risks, from assessment of carcinogenic and non- carcinogenic materials, were detected in the water. Hazard Quotation (HQ) and Hazard Index (HI) were lower than 1, in both seasons (wet and dry) for children and adults. Cancer Risks (CR) showed that they were in order of Cr>Ni>Pb>Cd from highest to lowest in both seasons for both adults and children. CR of Pb for adults and child recorded 21.95% (dry), 7.7% (wet) and 21.95% (dry), 4.8% (wet), respectively, in accordance with the recommended guideline of US EPA. 100% of Cr in both seasons for adults and children was recorded, where the sampled spring water exceeded the threshold limit. The level of Cd revealed in the study complied with the limit of CR in all sampled springs for both dry and wet seasons. Ni values of CR showed 100% for both seasons, for adults which complied with the recommended level, while with children, the values exceeded for both seasons. The statistical analysis showed that there was weak or no correlation between studied parameters in both seasons. There was significant difference found in most parameters of the average levels obtained during wet and dry seasons on spring water, such as total coliform, faecal coliform, temperature, pH, turbidity, Mo , As, Cr, Cu, Ni, Mn, Na ; Mg, Si, P, K , phosphate and nitrite (P<0.05). Those that showed no significant difference were E. coli, salinity, TDS, EC, Al, Hg, Pb, V , Co, Se, Sr, Sn, Sb , Cd, Fe, Zn, Ba, Cl, sulphate, fluoride, Br, nitrate (P>0.05). The Quantitative Microbiological Risk Assessment (QMRA) results showed, the risks of infection per-day results obtained for dry and wet season; these showed that for a child the range was 0 -2.38% (dry) and 0- 2.936% (wet), whereas for adults, the range was 0 - 26.566% (dry) and 0 - 27.459% (wet). There was a relatively high annual risk of infections observed in this study with highest values of 99.58% (child) and 98.80% (adult). The risk of illness values observed showed a range of 0-34.855% (adult) and 0-35 % (child), recorded at S24. This study also presented spatial distribution assessment of water quality to help with better mapping and managing of water quality parameter. The results provide useful data on the suitability of the use of spring water in Thulamela Municipality, hence, provide baseline information of water quality status of the study area. The study recommends that there should be proper treatment of spring water before consumption and increasing public awareness of local communities about spring water and its importance.
MESHWR
Department of Earth Sciences
Keywords: Spring water; UCTD; Water quality; Health risks; Trace elements; Use of spring water; 628.1660968; Water quality -- South Africa -- Limpopo; Water quality management -- South Africa -- Limpopo; Drinking water -- South Africa -- Limpopo; Drinking water -- Standards -- South Africa -- Limpopo; Drinking water -- Microbiology -- South Africa -- Limpopo